(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
With the adoption of single coil approach, printed spiral resonator design strategy for near-field wireless energy transfer is presented. A pair of symmetrical resonators operating at high frequency band specifically 6.78 MHz and 13.56 MHz is designed. Simulated power transfer efficiency (PTE) of over 88% are obtained for both frequencies when coupled spiral resonators separated at a distance of 25 mm is integrated with hybrid compensation network topology. The variance of PTE between both frequencies is about 0.04.